Predation risk and optimal foraging trade-off in the demography and spacing of the George River Herd, 1958 to 1993 - Bergerud, Arthur T.; Luttich, Stuart N. (Rangifer, 2003)
The behavior options of feeding animals lie on a continuum between energy maximization and minimization of predation risk. We studied the distribution, mobility, and energy budgets of the George River herd, Ungava from 1974 to 1993. We arranged the annual cycle into 6 phases where we argue that the importance between the priorities of optimal foraging and predation risk change between periods. At calving, risk is more important than foraging for females but males take more risk to optimally forage. During the mosquito season, insect avoidance takes priority over risk and for¬aging. Optimal foraging takes precedent over risk in the late summer and fall and it is at this time that the herd expanded its range relative to numbers and forage abundance. In the winter (December to mid-March) animals sought restricted localized ranges with low snow cover to reduce predation risk. The spring migration of females may have increased risk during the interval the females were moving back to the tundra to give birth to their neonates on the low risk calv¬ing ground. In May, females sought early greens near treeline, which may have increased risk in order to provide maximum nutrition to their fetuses in the last weeks of pregnancy. The ancestors of the George River Herd during the Pleistocene, 18 000 yr. BP may have reduced predation risk by spacing-out in the Appalachian Mountains, removed from the major specie of the megafauna in the lowlands. With global warming, it is argued the major problem for caribou will be increased wolf predation rather than changing forage and nutritional regimes. It is essential that First Nation residents of the North maintain their option to manage wolf numbers if excessive predation in the future adversely affects the migratory herds of the Northwest Territories and Ungava.